Penerapan Strategi SOAR untuk Mempertahankan Pangsa Pasar di Restoran Denny’s Senayan City - Putri Maulida; Asep Parantika; Lyly Soemarni (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2025)
This study aims to analyze the implementation of SOAR (Strengths, Opportunities, Aspirations, and Results) strategy in maintaining the market share of Denny's Senayan City Restaurant. The SOAR methodology was chosen because its approach is more proactive and based on internal strengths and external opportunities compared to other analysis methods such as SWOT which tend to focus on weaknesses and threats. This study uses SOAR analysis to identify Denny's main strengths of high-quality service and strategic location in a large shopping center. On the other hand, the lack of varied menu innovation is the biggest challenge that must be overcome to maintain customer interest. This study found that although Denny's has a strong foundation in terms of quality and location, Denny's needs to make improvements in terms of menu diversity and customer experience development. The practical implications of this study for Denny's restaurant owners are the importance of focusing on product innovation related to market trends and maintaining the right customer experience to stay competitive in a dynamic market.